Recurrence of stroke amongst women of reproductive age: impact of and on subsequent pregnancies. (1st February 2015) - Cruz‐Herranz, A.; Illán‐Gala, I.; Martínez‐Sánchez, P.; Fuentes, B.; Díez‐Tejedor, E.
<x xml:space="preserve">Abstract</x> Background and purpose The risk of recurrence of stroke after pregnancy is poorly known. Methods This was an observational study of women younger than 45 years of age with transient ischaemic attack (TIA), cerebral infarction (CI), cerebral venous thrombosis (CVT) or intracerebral hemorrhage (ICH) treated in a stroke unit (January 1996–2011). The clinical data were prospectively collected in a database. Information on reproductive history after stroke was obtained using telephone surveys (2011). The variables were demographic data, vascular risk factors, stroke type, outcomes, medical advice concerning pregnancies after stroke, number of pregnancies after stroke, neurological assessment during pregnancy, antithrombotic treatments during pregnancy/puerperium, fertility treatments administered and information about hemorrhagic/ischaemic stroke recurrence. Results Overall, 102 women were included: 24 TIA, 64 CI (four large vessel disease, 14 cardioembolic, 12 small vessel disease, 17 undetermined etiology, 17 uncommon etiology), 12 CVT and two ICH. Mean age at the time of first stroke was 35 (±7.5) years. Median follow‐up was 7.4 years (range 1–17). Thirty‐two pregnancies occurred in 27 patients (previous diagnosis: four TIA, 17 CI, five CVT and one ICH). One woman became pregnant using in vitro fertilization. Only eight pregnancies were followed up by a neurologist. Of 26 pregnancies without previous history of ICH, 18 (62%) underwent preventive antithrombotic treatment. No recurrence of stroke was observed during pregnancy/puerperium. Of the women without pregnancies after the first cerebrovascular event, four CIs and three TIAs were observed. Conclusion The recurrence of stroke after pregnancy is very low, which should be considered when counseling these patients.